Conservation or politics? Australia's target to kill 2 million cats. Issue 4 (19th February 2019) - Doherty, Tim S.; Driscoll, Don A.; Nimmo, Dale G.; Ritchie, Euan G.; Spencer, Ricky‐John
Abstract: The Australian Government's 5‐year Threatened Species Strategy contains four priority action areas and associated targets. Here, we argue that the well‐publicized target to cull 2 million feral cats has a weak scientific basis because: (1) reliable estimates of Australia's cat population size did not exist when the target was set; (2) it is extremely difficult to measure progress (numbers of cats killed) in an accurate, reliable way; and, most importantly, (3) the cull target is not explicitly linked to direct conservation outcomes (e.g., measured increases in threatened species populations). These limitations mean that the cull target fails to meet what would be considered best practice for pest management. The focus on killing cats runs the risk of distracting attention away from other threats to biodiversity, most prominent of which is widespread, ongoing habitat loss, which has been largely overlooked in the Threatened Species Strategy. The culling target is a highly visible symbol of a broader campaign around feral cat research and management in Australia, rather than a direct indicator of conservation action and success. We are concerned that progress toward the 2 million target could be misinterpreted as progress toward conserving threatened species, when the link between the two is not clear.